Remediation technologies for acid mine drainage: Recent trends and future perspectives. (January 2023) - Daraz, Umar; Li, Yang; Ahmad, Iftikhar; Iqbal, Rashid; Ditta, Allah
Abstract: Acid mine drainage (AMD) is a highly acidic solution rich in heavy metals and produced by mining activities. It can severely inhibit the growth of plants, and microbial communities and disturb the surrounding ecosystem. In recent years, the use of different bioremediation technologies to treat AMD pollution has received widespread attention due to its environment-friendly and low-cost nature. Various active and passive remediation technologies have been developed for the treatment of AMD. The active treatment involves the use of different chemical compounds while passive treatments utilize natural and biological processes like constructed wetlands, anaerobic sulfate-reducing bioreactors, anoxic limestone drains, vertical flow wetlands, limestone leach beds, open limestone channels, and various organic materials. Moreover, different nanomaterials have also been successfully employed in AMD treatment. There are also reports on certain plant growth-promoting rhizobacteria (PGPR) which have the potential to enhance the growth and productivity of plants under AMD-contaminated soil conditions. PGPR applied to plants with phytoremediation potential called PGPR-assisted phytoremediation has emerged as an economical and environment-friendly approach. Nevertheless, various approaches have been tested and employed, all the approaches have certain limitations in terms of efficiency, secondary pollution of chemicals used for the remediation of AMD, and disposal of materials used as sorbents or as phytoextractants as in the case of PGPR-assisted phytoremediation. In the future, more research work is needed to enhance the efficiency of various approaches employed with special attention to alleviating secondary pollutants production and safe disposal of materials used or biomass produced during PGPR-assisted phytoremediation. Graphical abstract: Image 1 Highlights: Acid mine drainage (AMD) severely inhibits plant growth and microbial communities. Active treatment technologies involve the use of different chemical compounds. Passive treatment technologies utilize natural and biological processes. Plant growth promoting rhizobacteria (PGPR) enhance plant biomass and phytoextraction. PGPR-assisted phytoremediation is an economical and eco-friendly approach.